Analisis Implementasi Kebijakan Revitalisasi Kawasan Alun-Alun Banten Lama Kota Serang dalam Rpjmd 2025 – 2029 - Assyifa Aulia Chandra; Laeli Nur Khanifah; Sofiyatunnisa Sofiyatunnisa; Diah Setiani; Nur Sofi Desnianum (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
The Banten Lama Square Area is part of a historical and religious tourism destination that plays a strategic role in supporting regional development in Serang City. To improve the quality of the area, the government implemented a revitalization policy in line with the Serang City Regional Medium-Term Development Plan (RPJMD) 2025–2029. This study aims to analyze the implementation of the revitalization policy of the Banten Lama Square Area using George C. Edward III’s policy implementation model, which consists of communication, resources, disposition, and bureaucratic structure. This research employed a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation involving informants from the Public Works and Spatial Planning Office (DPUPR) and the Youth, Sports, and Tourism Office (Disparpora) of Serang City. The findings indicate that the implementation of the revitalization policy has been carried out relatively well through inter-agency coordination, resource support, implementers’ commitment, and a clear division of responsibilities. The revitalization has also contributed positively to area management and tourism attractiveness. However, several challenges remain, including street vendor arrangement, drainage issues, and the need to strengthen coordination among stakeholders. Therefore, the success of the revitalization policy requires sustainable collaboration among government institutions, area managers, and the local community.